Adaptation Challenges Faced by New Cadets in Maritime Education: A Qualitative Study at Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta - Simanjuntak, Marudut Bernadtua; Ala, Asman; Simanjuntak, Ronald; Hamidi, Nazilul; Yoniessa, Siska (Innovative: Journal Of Social Science Research, 2023)
This research paper presents a comprehensive analysis of the challenges encountered by new cadets pursuing maritime education at Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta. The study focuses on three major study programs at STIP, namely Port & Shipping Management, Nautical, and Technical programs. The research utilises a descriptive qualitative approach to delve into the experiences of new cadets as they make the transition from regular senior high school to maritime education, particularly in a diverse and dynamic urban setting like Jakarta. The research primarily relies on in-depth document analysis and interviews with the new cadets, shedding light on the societal and cultural adaptations that are necessitated by their geographical origins. A significant proportion of these cadets originate from rural areas far from Jakarta, which adds a layer of complexity to their adaptation process. Through a rigorous examination of the data collected, this study unveils the multifaceted challenges faced by the new cadets. These challenges encompass not only the academic demands of their respective programs but also the social and cultural adjustments they must make. Moreover, this research underscores the pivotal role of STIP, one of the preeminent vocational maritime schools in Jakarta, in facilitating these adaptations and providing a conducive learning environment. The findings of this study offer valuable insights into the psychological and behavioural aspects of cadet adaptation in maritime education, with potential implications for educational policy and support systems. Understanding the challenges faced by new cadets is vital for enhancing their educational experiences and, ultimately, their success in the maritime industry.